(untitled) (Medical Forum Monthly, 2026)
Objective: This study compared the effects of a conventional sintering cycle (1500°C for 2h, total 11h) versus a short cycle (1500°C for 2h, total 4h) on the properties of a commercial 3Y-TZP (Upcera YZ HT). Study Design: Experimental analytical studyPlace and Duration of Study: This study was conducted at the Department of Prosthetic Dental Science, College of Dentistry, University of Najran, Saudi Arabia, from 1st June 2025 to 30th November 2025. Methods: Thirty bar-shaped specimens (n=15/group) were milled, sintered, and analyzed for flexural strength, grain size, and monoclinic phase content. Intergroup comparisons were performed using Student’s t-test and Mann– Whitney U-test. A p-value < 0.05 was considered statistically significant. Results: Results showed no statistically significant differences between groups: flexural strength (Conventional: 1309.42 ± 329.88 MPa; Short: 1187.23 ± 326.35 MPa; p=0.208), monoclinic phase content (Conventional: 47.92 ± 12.18%; Short: 50.42 ± 8.03%; p=0.84), or grain size (Conventional: 0.64 ± 0.18 μm; Short: 0.46 ± 0.08 μm; p=0.11). Correlations among these parameters were also non-significant. Conclusion: Within the study's limitations, the short sintering cycle yielded zirconia with comparable mechanical properties, phase stability, and a clinically acceptable microstructure to the conventional cycle. This supportsaccelerated sintering as a viable, technology-driven, time-efficient alternative for dental laboratories without compromising core material performance.